Multi-agent programming to enhance resiliency of earthquake-prone old metropolitan areas by transit-oriented development under public-private partnership - Soleimani, Hojjatollah; Poorzahedy, Hossain (European journal of transport and infrastructure research, 2021)
Deteriorated urban areas in large cities have poor living standards, are inaccessible and small-sized, and have unstable building structures. Earthquake hazards may turn such situations into human disasters. In most cases, neither the governments nor the owners of these properties have enough budgets for renovating them. The purpose of this paper is to take advantage of Transit Oriented Development concepts to simultaneously solve two major urban area problems: (a) renovation of deteriorated urban areas and prevention of urban sprawl, and (b) design of transit network and promotion of transit-oriented development to reduce traffic congestion, pollution, and other unwanted outcomes of the extensive automobile use in large metropolitan areas. This paper proposes a bilevel multi-agent programming in which each agent maximizes the respective benefits while being subjected to the results of the decisions by others. We formulate the problem and solve it by a novel meta-heuristic algorithm. After analyzing the set of solutions to a test problem, we apply the algorithm on this rather large, real case urban area, and discuss the results. The solution results indicate that the proposed methodology: (a) reduces the total travel time in transportation networks of the city, (b) turns the deteriorated urban developments into a new and attractive environment, (c) provides a profitable investment for the construction industries in the context of Build-Operate-Transfer scheme, and (d) upgrades urban life for the city in general, and alleviates earthquake hazards for the inhabitants of the deteriorated urban areas, in particular.